The rise and fall of neoliberalism : the collapse of an economic order? - Birch, Kean.; Mykhnenko, Vlad. (London : Zed Books, 2010)
The recent, devastating and ongoing economic crisis has exposed the faultlines in the dominant neoliberal economic order, opening debate for the first time in years on alternative visions that do not subscribe to a'free' market ethic. Bringing together the work of distinguished scholars and dedicated activists, The Rise and Fall of Neoliberalism presents critical perspectives of neoliberal policies, questions the ideas underpinning neoliberalism, and explores diverse responses to it from around the world.--From publisher description.
Includes bibliographical references and index.
Keywords: Neoliberalism; International economic relations; Economic policy; Global Financial Crisis, 2008-2009